2015
DOI: 10.1002/hon.2195
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B‐related serological events in hematopoietic stem cell transplant patients and efficacy of lamivudine prophylaxis against reactivation

Abstract: Reactivation of remote hepatitis B infection (RHBI) is an important cause of morbidity in hematopoietic cell transplant (HCT) patients. We analyzed the prevalence of RHBI in 205 patients who underwent HCT in our centre, serological events related to hepatitis B virus (HBV) reactivation and role of lamivudine prophylaxis in HCT patients with RHBI. The prevalence of RHBI was 14% (28/205 patients). Of these 28 patients, 15 received lamivudine prophylaxis (14 anti-HBcIgG positive and 1 only anti-HBs positive) whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Bowtie2 and Tophat2 were employed to map reads to the Homo sapiens GRCh38 genome ( Langmead and Salzberg, 2012 ; Kim et al, 2013 ). The mapped reads for each sample underwent assembly using StringTie ( Gupta et al, 2016 ). Subsequently, the transcriptomes from all samples were merged to reconstruct a comprehensive transcriptome, achieved through gffcompare ( https://github.com/gpertea/gffcompare/ ).…”
Section: Methodsmentioning
confidence: 99%
“…Bowtie2 and Tophat2 were employed to map reads to the Homo sapiens GRCh38 genome ( Langmead and Salzberg, 2012 ; Kim et al, 2013 ). The mapped reads for each sample underwent assembly using StringTie ( Gupta et al, 2016 ). Subsequently, the transcriptomes from all samples were merged to reconstruct a comprehensive transcriptome, achieved through gffcompare ( https://github.com/gpertea/gffcompare/ ).…”
Section: Methodsmentioning
confidence: 99%
“…Then sequence quality was also veri ed using fastp We used Bowtie2 30 and Tophat2 31 to map reads to the genome of Homo sapiens GRCh38. The mapped reads of each sample were assembled using StringTie 32 . Then, all transcriptome from all samples were merged to reconstruct a comprehensive transcriptome using gffcompare (https://github.com/gpertea/gffcompare/).…”
Section: Data Processingmentioning
confidence: 99%
“…Universal prophylactic anti-HBV therapy can prevent HBVr in HBsAg-negative, anti-HBc-positive patients undergoing HSCT [91,97,98,99]. However, in allo- and auto-HSCT with resolved HBV infection, a retrospective cohort study with a control group demonstrated that a short-term (median 7 months) of lamivudine prophylaxis was not sufficient to prevent HBV reactivation in a median time of 20 months after HSCT [70].…”
Section: Management Of Hbv Reactivationmentioning
confidence: 99%